Lack of autophagy in the hematopoietic system leads to loss of hematopoietic stem cell function and dysregulated myeloid proliferation. - Mortensen, M; Watson, A; Simon, A (2011)
The regulated lysosomal degradation pathway of autophagy prevents cellular damage and thus protects from malignant transformation. Autophagy is also required for the maturation of various hematopoietic lineages, namely the erythroid and lymphoid ones, yet its role in adult hematopoietic stem cells (HSCs) remained unexplored. While normal HSCs sustain life-long hematopoiesis, malignant transformation of HSCs or early progenitors leads to leukemia. Mechanisms protecting HSCs from cellular damage are therefore essential to prevent hematopoietic malignancies. By conditionally deleting the essential autophagy gene Atg7 in the hematopoietic system, we found that autophagy is required for the maintenance of true HSCs and therefore also of downstream hematopoietic progenitors. Loss of autophagy in HSCs leads to the expansion of a progenitor cell population in the bone marrow, giving rise to a severe, invasive myeloproliferation, which strongly resembles human acute myeloid leukemia (AML).